Modeling the impact of early vaccination in an influenza pandemic in the United States - Van Hung Nguyen; Pascal Crépey; B. Adam Williams; Verna L. Welch; Jean Marie Pivette; Charles H. Jones; Jane M. True (npj Vaccines)
Abstract We modeled the impact of initiating one-dose influenza vaccination at 3 months vs 6 months after declaration of a pandemic over a 1-year timeframe in the US population. Three vaccine effectiveness (VE) and two pandemic severity levels were considered, using an epidemic curve based on typical seasonal influenza epidemics. Vaccination from 3 months with a high, moderate, or low effectiveness vaccine would prevent ~95%, 84%, or 38% deaths post-vaccination, respectively, compared with 21%, 18%, and 8%, respectively following vaccination at 6 months, irrespective of pandemic severity. While the pandemic curve would not be flattened from vaccination from 6 months, a moderate/high effectiveness vaccine could flatten the curve if administered from 3 months. Overall, speed of initiating a vaccination campaign is more important than VE in reducing the health impacts of an influenza pandemic. Preparedness strategies may be able to minimize future pandemic impacts by prioritizing rapid vaccine roll-out.